Understanding Progressive Multifocal Leukoencephalopathy Risk in Multiple Sclerosis Patients Treated with Immunomodulatory Therapies: A Bird’s Eye View - Mills, Elizabeth A.; Mao-Draayer, Yang (Frontiers in Immunology, 2018)
The increased use of newer potent immunomodulatory therapies for Multiple Sclerosis (MS), including natalizumab, fingolimod, and dimethyl fumarate, has expanded the patient population at risk for developing progressive multifocal leukoencephalopathy (PML). These MS therapies shift the profile of lymphocytes within the central nervous system (CNS) leading to increased anti-inflammatory subsets and decreased immunosurveillance. Similar to MS, PML is a demyelinating disease of the CNS, but is caused by the JC virus. The manifestation of PML requires the presence of an active, genetically rearranged form of the JC virus within CNS glial cells, coupled with the loss of appropriate JC virus specific immune responses. The reliability of metrics used to predict risk for PML could be improved if all three components: viral genetic strain, localization, and host immune function, were taken into account. Advances in our understanding of the critical lymphocyte subpopulation changes induced by these MS therapies, and ability to detect viral mutation and reactivation will facilitate efforts to develop these metrics.